Comparison of the two time schedules for endoscopic sclerotherapy: a prospective randomised controlled study. Issue 6 (June 1986) - Sarin, S K; Sachdev, G; Nanda, R; Batra, S K; Anand, B S
Abstract : To compare the efficacy and safety of one week versus three weeks interval treatment schedules of endoscopic sclerotherapy, injections were carried out in a prospective manner in 96 patients with variceal bleeding; 47 on a one week and 49 on a three weeks treatment schedule. Weekly endoscopic sclerotherapy eradicated oesophageal varices significantly (p less than 0.01) earlier (mean +/- SD 7.1 +/- 2.43 weeks) as compared with the three weeks regimen (mean +/- SD 14.86 +/- 4.86 weeks). The rebleeding rate was also significantly less (p less than 0.05) with weekly endoscopic sclerotherapy (8.5%) as compared with three weeks endoscopic sclerotherapy treatment (26.5%). The amount of alcohol and the number of endoscopic sclerotherapy courses required for complete variceal eradication did not differ significantly between the two groups. Patients undergoing weekly injections were seen to have significantly more oesophageal ulcers (p less than 0.01) as compared with the three weeks group, necessitating at times (23%) postponement of the procedure. There was, however, no difference between the two groups in the frequency of oesophageal stricture formation, dysphagia, retrosternal pain, and fever. Mortality was also similar in the two groups. It can be concluded that a weekly schedule of endoscopic sclerotherapy appears superior to a three weeks schedule.